Noncoding RNAs Carried by Extracellular Vesicles in Endocrine Diseases. (1st April 2018) - Pomatto, Margherita A. C.; Gai, Chiara; Deregibus, Maria Chiara; Tetta, Ciro; Camussi, Giovanni
Abstract : RNA molecules are essential and fine regulators of important biological processes. Their role is well documented also in the endocrine system, both in physiological and pathological conditions. Increasing interest is arising about the function and the importance of noncoding RNAs shuttled by extracellular vesicles (EVs). In fact, EV membrane protects nucleic acids from enzyme degradation. Nowadays, the research on EVs and their cargoes, as well as their biological functions, faces the lack of standardization in EV purification. Here, the main techniques for EV isolation are discussed and compared for their advantages and vulnerabilities. Despite the possible discrepancy due to methodological variability, EVs and their RNA content are reported to be key mediators of intercellular communication in pathologies of main endocrine organs, including the pancreas, thyroid, and reproductive system. In particular, the present work describes the role of RNAs contained in EVs in pathogenesis and progression of several metabolic dysfunctions, including obesity and diabetes, and their related manifestations. Their importance in the establishment and progression of thyroid autoimmunity disorders and complicated pregnancy is also discussed. Preliminary studies highlight the attractive possibility to use RNAs contained in EVs as biomarkers suggesting their exploitation for new diagnostic approaches in endocrinology.